Answers

  • Brainly User
2016-01-07T23:01:51+08:00
Step 1:  Convert the radicals to to fractional exponent:

 \sqrt{3} = 3 ^{ \frac{1}{2} }

 \sqrt[3]{18}  18^{ \frac{1}{3} }

Step 2:  Convert the fractional exponents to similar fractions:

LCD of 1/2 and 1/3 is 6

1/2 = 3/6   ⇒ 3 \frac{1}{2} 3 ^{ \frac{3}{6} }

1/3 = 2/6   ⇒ 18 ^{ \frac{1}{3} }  = 18 ^{ \frac{2}{6} }

Step 3:  Convert to radicals:

 3^{ \frac{3}{6} } = \sqrt[6]{3 ^{3} }

18 ^{ \frac{2}{6} } = \sqrt[6]{18 ^{2} }

Step 4:  Multiply:

( \sqrt[6]{3 ^{3} } )( \sqrt[6]{18 ^{2} })

( \sqrt[6]{ 3^{3} })( \sqrt[6]{18 ^{2} } )= ( \sqrt[6]{ 3^{3} } )( \sqrt[6]{(3 ^{3})(12) }

 \sqrt[6]{(3 ^{6})(12) }

ANSWER  3\sqrt[6]{12}       








0